Extremes of body mass index and postoperative complications after esophagectomy. Issue 5 (29th March 2017) - Wightman, S. C.; Posner, M. C.; Patti, M. G.; Ganai, S.; Watson, S.; Prachand, V.; Ferguson, M. K.
SUMMARY: Obesity has been variously associated with reduced or similar rates of postoperative complications compared to normal weight patients undergoing esophagectomy for cancer. In contrast, little is known about esophagectomy risks in the underweight population. The relationship between the extremes of body mass index (BMI) and postoperative complications after esophagectomy was evaluated. Consecutive esophagectomy patients (2000–2013) were reviewed. The patients were stratified based on BMI at the time of diagnosis: underweight (<18.5), normal (18.5–24.9), overweight (25–29.9), obese I (30–34.9), and obese II or III (≥35). Hospital length of stay as well as postoperative complications and their accordion severity grading were evaluated according to the BMI category. Of 388 patients, 78.6% were male with a median age of 62 years at the time of operation. Pathologic cancer stage was 0 to I in 53%. BMI distribution was as follows: 5.6% underweight, 28.7% normal, 31.4% overweight, 22.8% obese I, and 11.5% obese II or III. Performance status was 0 or 1 in 99.2%. Compared to normal BMI patients, underweight patients had increased pulmonary complications (odds ratio (OR) 3.32, P = 0.014) and increased other postoperative complications (OR 3.00, P = 0.043). Patients who were overweight did not have increased complications compared to normal BMI patients. BMI groups did not differ in mortality rates or complication accordion severity grading. Hospital length of stay trended toward a longer duration in the underweight population ( P = 0.06). Underweight patients are at increased risk for postoperative pulmonary and other complications. Underweight patients may benefit from preoperative nutritional repletion and mitigation for sarcopenia. Aggressive postoperative pulmonary care may help reduce complications in these patients. In contrast, the operative risk in overweight and obese patients is similar to normal BMI patients.